FACING COVID-19 IN THE LIGHT OF THE MAXIM “NO HARM SHALL BE INFLICTED OR RECIPROCATED” (International Seminar on Syariah and Law (INSLA), 2020)
The Islamic legal maxim (al-qāʿidah al-fiqhiyyah) “no harm shall be inflicted or reciprocated” has become particularly significant in this era of pandemic. In the current context, this legal maxim is reasonably expected, provided that if they are adequately employed, to influence people’s choices and guide them to make certain decisions which are simultaneously religious and applicable for preservation of human life.This maxim is construed as prohibition of all actions that carry the notion of wronging, infringing on other’s rights, frustrating, overpowering, or setting back some party’s interests. In this article, we attempt to discern what Islamic jurisprudence has to say in this crucial combat which causes this global crisis. In light of the mentioned Islamic legal maxim, a flowchart that represents the sequence of the certain steps is derived, which is beneficial to be taken into consideration in the choices, decisions and actions related to or in the time of COVID-19.